Comparison of three galenic forms of lamivudine in young West African children living with Human Immunodeficiency Virus. Issue 6 (November 2021) - Pressiat, Claire; Dainguy, Evelyne; Tréluyer, Jean-Marc; Yonaba, Caroline; Urien, Saik; Eboua, François; Foissac, Frantz; Dahourou, Désiré Lucien; Bouazza, Naïm; Malateste, Karen; Desmonde, Sophie; Pruvost, Alain; et al.
Background: Few pharmacokinetic data were reported on dispersible tablets despite their increasing use. One hundred fifty HIV-infected children receiving lamivudine were enrolled in the MONOD ANRS 12, 206 trial. Three galenic forms were administered: liquid formulation, tablet form and dispersible scored tablet. Method: HIV-infected children <4 years old were enrolled in the MONOD ANRS 12, 206 trial designed to assess the simplification of a successful 12-months lopinavir-based antiretroviral treatment with efavirenz. Lamivudine plasma concentrations were analysed using nonlinear mixed effects modelling approach. Results: One hundred and fifty children (age: 2.5 years (1.9–3.2), weight 11.1 (9.5–12.5) kg (median (IQR)) were included in this study. Over the study period, 79 received only the syrup form, 29 children switched from syrup form to tablet 3TC/AZT form, 36 from syrup to the orodispersible ABC/3TC form and two from the 3TC/AZT form to the orodispersible ABC/3TC form. The 630 lamivudine concentrations were best described by a two-compartment model allometrically scaled. Galenic form had no significant effect on 3TC pharmacokinetic. Conclusion: This trial provided an opportunity to compare three galenic forms (liquid formulation, tablet form and dispersible scored tablet) of lamivudine in the target population of young HIV–1-infected children. Galenic form had no significant effect on lamivudine pharmacokinetics.